TAK1 mediates neuronal pyroptosis in early brain injury after subarachnoid hemorrhage - Xu, Pengfei; Tao, Chunrong; Zhu, Yuyou; Wang, Guoping; Kong, Lingqi; Li, Wenyu; Li, Rui; Li, Juanji; Zhang, Chao; Wang, Li; Liu, Xinfeng; Sun, Wen; et al. (Journal of neuroinflammation, 2021)
Background Innate immunity can facilitate early brain injury (EBI) following subarachnoid hemorrhage (SAH). Numerous studies suggest that pyroptosis could exacerbate extracellular immune responses by promoting secretion of inflammatory cytokines. Transforming growth factor-β-activated kinase 1 (TAK1) is a quintessential kinase that positively regulates inflammation through NF-κB and MAPK signaling cascades. However, the effects of TAK1 on neuroinflammation in EBI following SAH are largely unknown. Methods Two hundred and forty-six male C57BL/6J mice were subjected to the endovascular perforation model of SAH. A selective TAK1 inhibitor, 5Z-7-oxozeaenol (OZ) was administered by intracerebroventricular (i.c.v) injection at 30 min after SAH induction. To genetic knockdown of TAK1, small interfering RNA (siRNA) was i.c.v injected at 48 h before SAH induction. SAH grade, brain water content, BBB permeability, neurological score, western blot, real-time PCR, ELISA, transmission electron microscope, and immunofluorescence staining were performed. Long-term behavioral sequelae were evaluated by the rotarod and Morris water maze tests. Furthermore, OZ was added to the culture medium with oxyhemoglobin (OxyHb) to mimic SAH in vitro. The reactive oxygen species level was detected by DCFH-DA staining. Lysosomal integrity was assessed by Lyso-Tracker Red staining and Acridine Orange staining. Results The neuronal phosphorylated TAK1 expression was upregulated following SAH. Pharmacologic inhibition of TAK1 with OZ could alleviate neurological deficits, brain edema, and brain-blood barrier (BBB) disruption at 24 h after SAH. In addition, OZ administration restored long-term neurobehavioral function. Furthermore, blockade of TAK1 dampened neuronal pyroptosis by downregulating the N-terminal fragment of GSDMD (GSDMD-N) expression and IL-1β/IL-18 production. Mechanistically, both in vivo and in vitro, we demonstrated that TAK1 can induce neuronal pyroptosis through promoting nuclear translocation of NF-κB p65 and activating nucleotide-binding oligomerization domain (NOD)-like receptor pyrin domain containing 3 (NLRP3) inflammasome. TAK1 siRNA treatment mitigated SAH-induced neurobehavioral deficits and restrained phosphorylated NF-κB p65 expression and NLRP3 inflammasome activation. TAK1 blockade also ameliorated reactive oxygen species (ROS) production and prevented lysosomal cathepsin B releasing into the cytoplasm. Conclusions Our findings demonstrate that TAK1 modulates NLRP3-mediated neuronal pyroptosis in EBI following SAH. Inhibition of TAK1 may serve as a potential candidate to relieve neuroinflammatory responses triggered by SAH.